Biofortification in Ethiopia: Opportunities and challenges - Bachewe, Fantu Nisrane; Genye, Tirsit; Girma, Meron; Samuel, Aregash; Warner, James; van Zyl, Cornelia (SAGE Publications, 2023)
Children younger than 5 years and women of reproductive age often suffer from micronutrient deficiencies. Biofortification, which involves enriching staple crops with micronutrients, is a nutritional intervention focused on addressing micronutrient deficiencies. It is equitable, sustainable, and costs less than other nutritional interventions.This study investigates biofortification in Ethiopia, considering 6 globally biofortified crops, 5 of which are currently being biofortified in Ethiopia. However, only 2 of these crops are important in the consumption baskets of most Ethiopians. Therefore, efforts to mainstream biofortification should begin with studies to identify crops that have larger impacts in reducing local micronutrient deficiencies and their cost-effectiveness.Literature was searched between July and December 2021 using Google Scholar to provide insights into the state of biofortification in Ethiopia. Key-informant interviews were conducted to gain insights into the state of biofortification in Ethiopia and to identify bottlenecks for scaling up the production and consumption of biofortified foods. Furthermore, Annual Agriculture Sample Survey and 2015/16 Ethiopian Household Consumption and Expenditure Survey data were used to describe the area under production of biofortifiable crops and their importance in total consumption, respectively.Mainstreaming biofortification in Ethiopia faces several challenges. Policy documents appear to be inconsistent, regressive, and vague regarding biofortification. Critically, there is no specific institution to oversee and/or coordinate biofortification-related activities.Overall, the success of biofortification depends upon a strong coordination body with clear mandates from detailed policies; adequate funding for research and development; and robust monitoring and evaluation of the identified production, adoption, and consumption issues.